Molecular typing of Argentinian Mycobacterium avium subsp. paratuberculosis isolates by multiple-locus variable number-tandem repeat analysis - Gioffré, Andrea (2015)
Multiple-locus variable number-tandem repeat analysis (MLVA) of Mycobacterium avium subspecies paratuberculosis (MAP) isolates may contribute to the knowledge of strain diversity in Argentina. Although the diversity of MAP has been previously investigated in Argentina using IS900-RFLP, a small number of isolates were employed, and a low discriminative power was reached. The aim of the present study was to test the genetic diversity among MAP isolates using an MLVA approach based on 8 repetitive loci. We studied 97 isolates from cattle, goat and sheep and could describe 7 different patterns: INMV1, INMV2, INMV11, INMV13, INMV16, INMV33 and one incomplete pattern. INMV1 and INMV2 were the most frequent patterns, grouping 76.3% of the isolates. We were also able to demonstrate the coexistence of genotypes in herds and co-infection at the organism level. This study shows that all the patterns described are common to those described in Europe, suggesting an epidemiological link between the continents.